Visualization of bivariate sequence length-chain length distribution in free radical copolymerization - Saeb, Mohammad Reza; Mohammadi, Yousef; Rastin, Hadi; Kermaniyan, Tayebeh Sadat; Penlidis, Alexander (Wiley, 2017)
Copolymer properties and processability depend on copolymer microstructure, i.e., copolymer composition and monomer unit arrangements along copolymer chains. To predict ultimate properties of copolymers, one needs complete information on the length and position of sequences of each monomer type, M1 and M2, in every polymer chain in the system. A versatile Kinetic Monte Carlo (KMC) code has been developed and applied for the simulation of typical free radical copolymerizations. The code allows explicit monitoring of every growing chain during the course and at the end of polymerization, and can account for comonomer systems of any arbitrary reactivity ratios (r1 and r2) over the full range of monomer composition. Meanwhile, it eliminates the need for solving arrays of differential equations arising from deterministic modeling approaches. Since the code virtually synthesizes billions of copolymer molecules and keeps in storage information on each and every copolymer chain in the system, it allows for detailed statistical analysis. The simulator visualizes the bivariate sequence length-chain length (SL-CL) distribution for typical copolymerization systems and examples with: r1<1 & r2<1; r1>1 & r2<1; (r1 x r2) = 1; and r1=r2=1, and is also applied successfully to an experimental scenario described in the literature.
Keywords: Monte Carlo simulation; Copolymerization; Chain length-Sequence length distribution; Molecular architecture; Tailor-made copolymers